The Structure of Interdisciplinary Science - Hvidtfeldt, Rolf (New Directions in the Philosophy of Science, 2018)
This book presents a novel approach to the analysis of interdisciplinary science based on the contemporary philosophical literature on scientific representation. The basic motivation for developing this approach is that epistemic issues are insufficiently dealt with in the existing literature on interdisciplinarity. This means that when interdisciplinary science is praised (as it often is), it is far from clear to what extent this praise is merited - at least if one cares about various more or less standardised measures of scientific quality. To develop a more adequate way of capturing what is going on in interdisciplinary science, I draw inspiration from the rich philosophical literature on modelling, idealisation, perspectivism, and scientific pluralism. The discussion hereof reveals a number of critical pitfalls related to transferring mathematical and conceptual tools between scientific contexts, which should be relevant and interesting for anyone actively engaged in funding, evaluating, or carrying out interdisciplinary science.